2009
DOI: 10.1016/j.bmcl.2008.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of a human monoclonal neutralizing antibody for Clostridium Botulinum neurotoxin serotype B

Abstract: Botulinum neurotoxins (BoNTs) are causative agents for botulism and are identified as a category A bioterror agents by the Centers for Disease Control and Prevention (CDC). Current antitoxins against BoNTs intoxication have some limitations including side effects or limited supply. As an alternative, neutralizing monoclonal antibodies will play an increasing role as BoNTs therapeutics. To date, no human anti-BoNT/B neutralizing monoclonal antibodies have yet to be reported. Herein, we describe an improved sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…This is a first kind of report which shows that the antibody raised against the light chain are able to prevent the blockage of acetylcholine release by in-vitro studies using PC-12 neuronal cells. Similar kind of studies were reported in BoNT/B HC domain (1088-1295) as antigen to screen BoNT/B neutralizing potency by a sensitive in-vitro cell-based assay with primary rat spinal cord (RSC) cells and the results indicates that a 1,000-fold molar excess of the Fab F2 was required for inhibition of BoNT/B activity and it concluded that this Fab possesses weak neutralization activity [38].…”
Section: Estimation Of Acetylcholine Releasementioning
confidence: 62%
“…This is a first kind of report which shows that the antibody raised against the light chain are able to prevent the blockage of acetylcholine release by in-vitro studies using PC-12 neuronal cells. Similar kind of studies were reported in BoNT/B HC domain (1088-1295) as antigen to screen BoNT/B neutralizing potency by a sensitive in-vitro cell-based assay with primary rat spinal cord (RSC) cells and the results indicates that a 1,000-fold molar excess of the Fab F2 was required for inhibition of BoNT/B activity and it concluded that this Fab possesses weak neutralization activity [38].…”
Section: Estimation Of Acetylcholine Releasementioning
confidence: 62%
“…The 50-kDa C-terminal fragment of the HC, known as the binding domain, recognizes surface receptors on target neurons, thus provoking the transmembrane internalization of the whole toxin [4,5]. Botulism can be prevented by the presence of neutralizing antibodies (or vaccination) against the botulinum neurotoxins [1]. The current formalin-inactivated pentavalent vaccine for botulism is effective, but this vaccine requires large scale production of the highly toxic material, which involves extensive treatment with formalin [6].…”
Section: Introductionmentioning
confidence: 99%
“…The botulinum neurotoxins (BoNTs), synthesized by a family of seven toxinotypes (A-G), are responsible for potent food intoxication known as botulism, which is a severe neuroparalytic disease [1]. BoNTs possess similar structures but are immunologically distinct, each of which is expressed as the single polypeptide chain of 150 kDa [2].…”
Section: Introductionmentioning
confidence: 99%
“…Effective treatment for botulism involves the timely administration of neutralizing antitoxin and several commercial preparations are available for treatment of humans [ 8 ], including infant botulism [ 9 ]. New countermeasures in development include human or humanized recombinant monoclonal antibodies [ 10 , 11 , 12 , 13 ]. The traditional mouse lethality or systemic toxicity neutralization test for determination of the potency of therapeutic antitoxins has been considered at the forefront for replacement on ethical grounds [ 14 ].…”
Section: Introductionmentioning
confidence: 99%